2021
DOI: 10.3390/cryst11060613
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Magnetic Properties Study of Fe2O3/NiO/Ni2FeO4 Nanocomposites

Abstract: In the current work, the nanocomposites that consist chiefly of three components—α-Fe2O3, NiO and Ni2FeO4, in two different ratios 2:2:1 (FNN-221) and 2:1:1 (FNN-211), respectively—were produced. The synthesis was done in two steps by following the chemical co-precipitation and mechanical ball-milling route. The presence of individual phase was identified from the XRD data without the detection of any additional impurities. The phase fraction of each component estimated from the profile fitting of XRD patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In recent years, there has been a surge of interest in composite nanomaterials because of the synergistic effect and size reduction induced enhancement of several properties that find usefulness in various applications [1][2][3]. Remya et al [4] reported the enhancement of the electrical and magnetic properties of BiFeO 3 /MnFe 2 O 4 NCs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, there has been a surge of interest in composite nanomaterials because of the synergistic effect and size reduction induced enhancement of several properties that find usefulness in various applications [1][2][3]. Remya et al [4] reported the enhancement of the electrical and magnetic properties of BiFeO 3 /MnFe 2 O 4 NCs.…”
Section: Introductionmentioning
confidence: 99%
“…The CoFe 2 O 4 /PVA-SiO 2 NCs are shown to be useful in magnetic and photocatalytic applications [7]. Among several NCs, the multi-phasic magnetic nanoparticles have attracted profound attention among researchers as the magnetic properties of such materials are intensely connected with the contact between differently ordered magnetic phases along with the interfacial interactions [3,8]. As the properties can be tailored via manipulating synthesis conditions [9], chemical compositions and phase fractions of components [3,4,10,11], magnetic NCs find applications in energy storage devices [12], spintronic devices [13], magnetic contrast agent [14], catalyst [15], high-density magnetic storage media [16], Li-ion batteries [17,18], drug delivery [6], permanents magnets [19][20][21], etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17,18]. Nickel oxide nanostructures, in particular nanotubes, nanoparticles and nanowires, offer even a greater value [19].…”
Section: Introductionmentioning
confidence: 99%
“…Metal oxides have been the subject of many studies due to their excellent photocatalytic properties. TiO2 [1,2], NiO [3,4], Ga2O3 [5,6], MgO [7,8], CdO [9,10], etc. semiconductors are widely studied.…”
Section: Introductionmentioning
confidence: 99%